2004
DOI: 10.17221/5736-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni: Public health hazards and potential control methods in poultry: a review

Abstract: Certain strains of Campylobacter jejuni are implicated not only in diarrhea in humans, but also in the rare, but more serious Guillain-Barré syndrome, which may be fatal. Since poultry are the major reservoirs of C. jejuni, reducing contamination of poultry meat with this organism will decrease risk to the human consumer. Poultry meat which is contaminated with Campylobacter spp. and other human enteropathogens is safe for human consumption if handled properly while raw, and cooked completely. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…Because the modulation of gut microflora by dietary DFM in chickens is well-documented (Hariharan et al, 2004;Nava et al, 2005;Yang et al, 2009), the DFM used in this study were selected under the presumption that they act by decreasing the intestinal load of harmful bacteria, thereby promoting gut function, increasing immunity-mediated pathogen protection and nutrient absorption, and enhancing weight gain. In this regard, future studies using broilers fed with less digestible diets, reared under field conditions or exposed to common enteric infections, or both, may delineate a positive effect of dietary DFM on growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Because the modulation of gut microflora by dietary DFM in chickens is well-documented (Hariharan et al, 2004;Nava et al, 2005;Yang et al, 2009), the DFM used in this study were selected under the presumption that they act by decreasing the intestinal load of harmful bacteria, thereby promoting gut function, increasing immunity-mediated pathogen protection and nutrient absorption, and enhancing weight gain. In this regard, future studies using broilers fed with less digestible diets, reared under field conditions or exposed to common enteric infections, or both, may delineate a positive effect of dietary DFM on growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of pre- and pro-biotics, i.e., complex polysaccharides and strains of lactic acid bacteria, has shown some promise (Hariharan et al, 2004), and could be examined further. Competitive exclusion (Nurmi principle), generally successful for control of salmonellae, has not always been successful for controlling campylobacters (Mead, 2002).…”
Section: Control Strategiesmentioning
confidence: 99%
“…Poultry remains the most important reservoir and source for human infections (van Vliet and Ketley, 2001). The normal body temperature of fowl is 41 to 42°C, which coincides with the optimum growth temperature of thermophilic Campylobacter species (Corry and Atabay, 2001;Engvall, 2001;Petersen et al, 2001;Hariharan et al, 2004). An European food safety authority report (EFSA, 2010) demonstrated that approximately 80% of chicken carcasses of the European Union market are contaminated with Campylobacter, whereas Salmonella was detected in only 16% of chicken carcasses in 22 EU countries.…”
Section: Introductionmentioning
confidence: 99%